2013
DOI: 10.31729/jnma.2117
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Postnatal Mother in Newborn Care

Abstract: Introduction: Neonatal mortality has continued to increase as a percentage (>60%) of overall infant mortality. Any further reduction in infant mortality is dependent on saving more newborn lives. It is possible if their mothers are knowledgeable and provide proper newborn care. Therefore, the objective of the study was to find out knowledge and practice of the postnatal mothers about newborn care.Methods: A descriptive study was done among 100 purposively selected post natal mothers admitted in Teaching Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 4 publications
5
29
3
4
Order By: Relevance
“…A study done by Shrestha et al also showed similar findings. 9 With regards to immunization, only 8% of the mothers had adequate knowledge on various aspects of immunization. Even though 93% of the babies were completely immunized as of date nearly 76% of the mothers were not aware of the names of the individual vaccines/supplements given for the newborn babies.…”
Section: Resultsmentioning
confidence: 99%
“…A study done by Shrestha et al also showed similar findings. 9 With regards to immunization, only 8% of the mothers had adequate knowledge on various aspects of immunization. Even though 93% of the babies were completely immunized as of date nearly 76% of the mothers were not aware of the names of the individual vaccines/supplements given for the newborn babies.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted within Tribhuvan University Teaching Hospital in Kathmandu Valley assessed newborn care knowledge and practices of 100 post‐partum mothers; health personnel, especially nurses, were found to have played a large role in encouraging mothers to initiate breastfeeding within 1 hour (Shrestha et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Postnatal dönemdeki annelerin bebek bakımı konusundaki bilgi ve uygulamalarının değerlendirildiği bir çalışmada katılımcıların %60'ının göbek kordonunun temiz ve kuru tutulması gerektiğini düşündükleri belirlenmiştir. 1…”
Section: Annelerinunclassified
“…Yenidoğanların yaşatılması binyıl gelişim hedeflerinin başarılması ve çocuğun sağlık durumunun geliştirilmesinde önemli bir yer tutar. 1 Dünya Sağlık Örgütü (DSÖ) tarafından, yenidoğanların morbidite ve mortalitesinin düşürülebilmesi için bebeklerin emzirilmesi, göbek bakımı, genel hijyeni, alt bakımı, ilk banyo zamanları ve periyodik aşıları gibi önemli yaşamsal hususların sürekli geliştirilmesi tavsiye edilmiştir. 2,3 Doğum sonu dönemde annenin yaşadığı fizyolojik ve psikolojik değişikliklere uyum sağlaması, annelik rolü, bebeğini kabullenmesi ve eve gittiğinde kendine ve bebeğine bakabilmesi için gerekli bilgi ve becerileri kazanması gerekir.…”
Section: Introductionunclassified